Drill Method to Improve Diabetic Ulcer Treatment Competency - Diah Merdekawati; Ani Astuti (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2018)
ABSTRACTIntroduction: Adolescents who get social media addiction, dopamine discharges occur in their bodies that create anxious feelings that can cause problems in social behavior in schools, living quarters, and peer social environments, and even trigger criminal acts such as defamation, slander, kidnapping, and fraud. The purpose of this research was to analyze the relationship between social media addiction and anxiety and the risk of social health disasters in adolescents. Methods: This research method is quantitative analytic descriptive with a cross-sectional design. The number of research samples was 79 students from the total population of 385 one of the junior high school students in the Yogyakarta region of Indonesia. Data retrieval technique in this research uses Stratified Random Sampling technique. Data on social media addiction, anxiety and the risk of social health disaster were collected using questionnaires and analyzed by Spearman Rank Test, a numerical correlation statistical test, with SPSS 21. Results: The results showed that the mean value of the age variable was 13.91, social media addiction was 60.38, anxiety was 14.46, and the risk of social health disaster was 67.97. The results of the statistical hypothesis test obtained that there was no significant relationship between social media addiction, anxiety, and social health disaster risk variables in adolescents. Conclusions: The conclusion of this research obtained that social media access can cause negative and positive impacts. Anxiety and the risk of social health disasters events are thought to be influenced by external factors.